The Improvement of Hydrophilic Property of Polyethersulfone Membrane with Chitosan as Additive - Fathanah, Umi; Machdar, Izarul; Riza, Medyan; Arahman, Nasrul; Lubis, Mirna Rahmah; Yusuf, Mukramah (Jurnal Rekayasa Kimia & Lingkungan, 2020)
Membrane technology has been implemented broadly for clean water treatment. To produce a better membrane, modification is carried out by adding chitosan into a polymer solution. Materials used in this research are polyethersulfone (PES) 18%, the n-methyl pyrrolidone solvent modified with a chitosan solution (at 0.2 1 wt%) as an additive, and deionized water as a non-solvent. The membrane synthesis is carried out with the non-solvent induced phase separation method of blending the polymer. Membrane characterization includes functional group analysis, morphological structure, and water contact angle. Membrane performance is monitored at the filtration process, resulting in the permeability coefficient, and for the rejection of a contaminant (humic acid) with dead-end filtration. Research results show that the modified membrane characterization has an asymmetric morphological structure with a thinner top layer, and the membrane sublayer has a finger-like macrovoid structure with a larger size as compared to the original PES membrane (without the chitosan solution addition). The chitosan additive into the PES membrane improves the membranes hydrophilic property. The highest value of the permeability coefficient is achieved with a 1% chitosan addition, which provides a permeability coefficient value of 10.524 L/m2.h.bar and a rejection coefficient of 70.3%.